Wireless resource allocation for distributed caching system:motivation, challenge and solution - Li WANG; Zhiyong FENG; Ping ZHANG (Dianxin kexue)
The diversified development and popularization of the mobile social network platform has made the demand of data transmission for mobile users show an explosive growth trend,and put forward new challenges to the lack of spectrum resources and the management of high load base stations. To solve such problems, the distributed caching system was introduced into the wireless collaboration network by allowing users to cache popular content items cooperatively, for effective content sharing among users with low energy consumption,high reliability and low latency,while offloading base station and backhaul data traffic. Firstly, the challenges and problems for wireless resource allocation in wireless distributed caching system were analyzed.Graph and matching theory based on methodologies were discussed to solve the resource management problems in terms of energy efficiency,spectral efficiency and secure transmission respectively.In addition,the feasibility of mining and using social information to improve the efficiency of wireless resources was discussed and analyzed, which provided a brief outlook on future interdisciplinary research between social science and wireless network.